2019
DOI: 10.1002/dev.21845
|View full text |Cite
|
Sign up to set email alerts
|

Mother–child adrenocortical synchrony: Roles of maternal overcontrol and child developmental phase

Abstract: An increasing amount of empirical attention is focused on adrenocortical synchrony as an index of biobehavioral co‐regulation between parent and child in the context of early child development. Working with an ethnically diverse community sample of children (N = 99, 50.5% male, ages 9–12), we collected saliva samples from mother–child dyads prior to and after a laboratory‐based performance challenge task, and tested whether maternal overcontrol and child age moderated dyadic synchrony in cortisol. Results reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 97 publications
0
11
0
Order By: Relevance
“…Few studies, however, address the reciprocal physiological links between the parent and child during this developmental transition, instead most have focused on early and middle childhood. A recent study with children in middle childhood showed that maternal characteristics and child age moderated mother-child cortisol attunement (Borelli et al, 2019). Furthermore, the limited research on parent-adolescent dyads affords minimal insights into the role that physiological cascades play.…”
Section: Stress Responses and Adrenocortical Attunementmentioning
confidence: 99%
“…Few studies, however, address the reciprocal physiological links between the parent and child during this developmental transition, instead most have focused on early and middle childhood. A recent study with children in middle childhood showed that maternal characteristics and child age moderated mother-child cortisol attunement (Borelli et al, 2019). Furthermore, the limited research on parent-adolescent dyads affords minimal insights into the role that physiological cascades play.…”
Section: Stress Responses and Adrenocortical Attunementmentioning
confidence: 99%
“…When the same research group asked adolescents to rate their parents’ emotions after a conflict discussion, stronger adrenocortical synchrony during the discussion was associated with less deactivation of posteromedial brain regions involved in the default mode network and social cognition (Saxbe et al, 2015a), suggesting a better ability to reflect on others’ emotions. Others found that adrenocortical synchrony was associated with lower maternal overcontrol during a challenging puzzle task (Borelli et al, 2019). However, adrenocortical synchrony has also been suggested as a potential mediator for the intergenerational transmission of risk for psychopathology in war-exposed families (Halevi et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…However, adrenocortical synchrony has also been suggested as a potential mediator for the intergenerational transmission of risk for psychopathology in war-exposed families (Halevi et al, 2017). Still, the two studies that use multilevel modeling strategies tend to suggest that adrenocortical synchrony is associated with better Parent×Adolescent interaction quality and greater adolescent emotion awareness (Borelli et al, 2019; Saxbe et al, 2015a). Though no strong conclusions can be drawn from two studies, future research should expand upon these findings and the similarly positive (though preliminary) findings for adrenocortical synchrony across all developmental periods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from investigations testing other forms of health functioning and collective biopsychosocial responses in particular contexts and interpersonal dynamics within and beyond families lend support for this line of inquiry. New work has suggested physiological synchrony (adrenocortical) among mother-child dyads as a potential indicator of biobehavioral coregulation (Borelli et al, 2019). In addition, among parent-adolescent dyads, suppression of emotions in one member of the dyad was associated with emotional eating in the other member (in addition to actor effects; Ferrer et al, 2017).…”
Section: Partner Effectsmentioning
confidence: 99%